Le regard féminin : une révolution à l'écran - Brey, Iris (Les Feux, 2609-8113, 2020)
Iris Brey théorise le regard féminin, ou female gaze, une façon de filmer les femmes sans en faire des objets, de partager la singularité des expériences féminines avec tous les spectateurices, quel que soit leur genre, et de renouveler notre manière de désirer en regardant sans voyeurisme. Des joyaux du cinéma à certaines oeuvres plus confidentielles, en passant par quelques séries et films très contemporains, Iris Brey nous invite à nous interroger sur le sens caché des images.
Keywords: approches et analyses; cinéma; com5170; communication; corps; cours; discipline; discours dominant; fem1300; fem3200; premier cycle; regard féminin; sexisme; systèmes d'oppressions; thématiques; violences

J'haïs les féministes: le 6 décembre 1989 et ses suites - Blais, Mélissa (Les éditions du remue-ménage, 2009)
«J’haïs les féministes», la déclaration de Marc Lépine au moment d’ouvrir le feu sur des étudiantes de l’école Polytechnique le 6 décembre 1989, a suscité une vive controverse, répercutée dans les médias dès le lendemain de la tragédie. Pourtant, 20 ans plus tard, cet événement qui a profondément marqué la mémoire collective est toujours absent des livres d’histoire du Québec. S’inscrivant à même le travail de mémoire, cet ouvrage, à travers une étude minutieuse des médias (en particulier, des quotidiens La Presse, Le Devoir et The Globe and Mail), retrace l’évolution des réactions à la tuerie. Mélissa Blais s’intéresse aux multiples explications du geste de Marc Lépine, et défend les analyses et discours féministes, nés dans l’urgence, puis violemment discrédités ou détournés, malgré les intentions clairement exprimées par le tueur. Elle examine également les principales commémorations, notamment celles entourant le 10e anniversaire, et consacre un chapitre au film Polytechnique sorti en 2009. «J’haïs les féministes»: le 6 décembre 1989 et ses suites éclaire les débats entre féminisme et antiféminisme encore présents derrière cette tragédie
Keywords: amériques; antiféminisme; approches et analyses; chantier antiféminisme RéQEF; communication; cours; discipline; fem1000; histoire; médias; premier cycle; québec; régions géographiques; sciences humaines; thématiques; violences

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communication; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; premier cycle; psychanalyse; queer; régions géographiques; sciences humaines; thématiques; violences; états-unis; études culturelles

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis